(2^3×3^2)^115×(3^3×2^2)115÷(3^4×2^4)115
Răspunsuri la întrebare
Răspuns de
5
(2^3×3^2)^115×(3^3×2^2)^115÷(3^4×2^4)^115 =
(2^3 × 3^2 × 3^3 × 2^2)^115 : (3^4 × 2^4)^115 =
( 2^5 × 3^5)^115 : (3^4 × 2^4)^115 =
(2^5 : 2^4 × 3^5 : 3^4)^115 =
( 2 × 3)^115 =
6^115
_____
(2^3 × 3^2 × 3^3 × 2^2)^115 : (3^4 × 2^4)^115 =
( 2^5 × 3^5)^115 : (3^4 × 2^4)^115 =
(2^5 : 2^4 × 3^5 : 3^4)^115 =
( 2 × 3)^115 =
6^115
_____
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă